Buy one for your banker - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Credit Guarantees: An Assessment of the State of Knowledge and New Avenues of Research. FAO. 1998. 127 pp. ISBN 92 5 104173 3. $11.00, e 10.60 FAO Publications See FAO reference elsewhere in this section for address.